Practical health co-operation – a cluster randomised study. The impact of referral templates on quality of care and health care co-operation between primary and secondary care - Wåhlberg, Henrik (UiT The Arctic University of Norway, 2019)
The referral represents the handing over of care from the general practitioner to the hospital specialist. In this PhD project a study was performed to assess whether an improved referral could lead to improved quality of care. A cluster randomised trial with the general practitioner surgery as the clustering unit was performed. Fourteen surgeries in the area surrounding the University Hospital of North Norway Harstad were randomised stratified by town versus countryside location. The intervention consisted of implementing referral templates for new referrals in four clinical areas: dyspepsia; suspected colorectal cancer; chest pain; and confirmed or suspected chronic obstructive pulmonary disease. The control group followed standard referral practice. Quality of the treatment pathway, as assessed by newly developed quality indicators, was used as the main outcome. Secondary outcomes included subjective quality assessment, adequacy of prioritisation and patient experience. Assessment of outcomes was done at the individual level. The patients, hospital doctors and outcome assessors were blinded to the intervention status. A total of 500 patients were included, with 281 in the intervention and 219 in the control arm. Referrals in the intervention group scored 18 % higher (95 % CI (11 %, 25 %), p < 0.001) on the referral quality score than the control group. The effect of the intervention on the quality indicator score was insignificant at 1.80% (95% CI, −1.46 to 5.06, p = 0.280). No significant differences between the intervention and the control groups were seen in the secondary outcomes. Active use of the referral intervention was low, estimated at approximately 50%. In this study improved referral quality did not lead to improved quality of care or prioritization. The results were hindered by a limited uptake of the intervention at GP surgeries and inconsistencies in outcome assessment.